Effectiveness of Chin-tuck Maneuver to Facilitate Swallowing in Neurologic Dysphagia - Saconato,Mariana (2016)
Introduction The chin-tuck maneuver is the most frequently employed postural maneuver in the treatment of neurogenic oropharyngeal dysphagia caused by encephalic vascular strokes and degenerative diseases. Objective The purpose of this study was to investigate the effectiveness of this maneuver in patients with neurogenic dysphagia and factors that could interfere in it. Methods In this retrospective cohort, we analyzed the medical files and videofluoroscopy exams of 35 patients (19male - 54% and 16 female - 46%; age range between 20 and 89 years old; mean = 69 years). Results The results suggest that the effectiveness of chin-tuck maneuver is related to the overall degree of dysphagia: the more severe the dysphagia, the less effective the maneuver. Conclusion Chin-tuck maneuver should benefit dysphagic patients with delay in the swallowing trigger, reduced laryngeal elevation, and difficulties to swallow liquids, but is not the best compensatory strategy for patients with severe dysphagia.